Critical air pollutant assessments and health effects attributed to PM2.5 during and after COVID-19 lockdowns in Iran: application of AirQ+ models - Ghobakhloo, Safiye; Khoshakhlagh, Amir Hossein; Mostafaii, Gholam Reza; Chuang, Kai-Jen; Gruszecka-Kosowska, Agnieszka; Hosseinnia, Pariya (Frontiers in Public Health, 2023)
Abstract Objectives: This study aimed to evaluate changes in Air Quality Index (AQI) values before, during, and after lockdown, as well as to evaluate the number of hospitalizations due to respiratory and cardiovascular diseases attributed to atmospheric PM2.5 pollution in Semnan City, Iran in 2019 to 2021 during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Daily air quality records were obtained from the global air quality index project and the US Environmental Protection Administration (EPA). In this research, the AirQ+ model was used to quantify health consequences attributed to particulate matter with an aerodynamic diameter of <2.5 µm (PM2.5). Results: The results we obtained showed positive correlations between air pollution levels and reductions in pollutant levels during and after the lockdown. PM2.5 was the critical pollutant for most days of the year, as its AQI was the highest among four investigated pollutants on most days. Mortality rates from chronic obstructive pulmonary disease (COPD) attributed to PM2.5 in the years 2019 2021 were 25.18% in 2019, 22.55% in 2020, and 22.12% in 2021. Mortality rates and hospital admissions due to cardiovascular and respiratory diseases decreased during the lockdown. The results showed a significant decrease in the percentage of days with unhealthy air quality in short-term lockdown in Semnan with moderate air pollution. Natural mortality (due to all natural causes) and other mortalities related to COPD, ischemic heart disease (IHD), lung cancer (LC), and stroke attributed to PM2.5 in the years 2019 2021 decreased. Conclusions: Our results support the general finding that anthropogenic activities cause significant health threats, which were paradoxically revealed during a global health crisis/challenge.